A meta analysis of the acupoint catgut embedding in the treatment of functional constipation - Zhao, Yufei; Wang, Zhiwei; Kuang, Shangke; Zhang, Shuxin (Frontiers in Medicine, 2025)
ObjectiveTo evaluate the efficacy and safety of acupoint embedding for FC by meta-analysis, in order to provide evidence-based medical evidence for clinical practice.MethodsA comprehensive literature search was conducted in China National Knowledge Infrastructure, WanFang, VIP, PubMed, Web of Science and The Cochrane Library for randomised controlled trials (RCTs) on ACE for FC published from inception to November 2024. The included studies were assessed for quality using the modified Jadad scale, and statistical analysis was performed using RevMan 5.4.1 and Stata BE 17.ResultsA total of 23 studies involving 1,794 patients were included. The meta-analysis showed that the total effective rate of ACE was significantly higher compared with oral Western medicine (odds ratio [OR] = 2.71, 95% confidence interval [CI]: 1.91–3.83, p < 0.00001), acupuncture (OR = 2.90, 95% CI: 1.68–5.01, p = 0.0001) and placebo groups (p < 0.05). There was no significant difference between ACE and oral Chinese medicine (OR = 2.34, 95% CI: 0.79–6.89, p = 0.12). The incidence of adverse reactions in the ACE group was low, presenting mainly as mild local discomfort such as soreness, bruising and pain, which were self-limiting.ConclusionAcupoint catgut embedding demonstrates superior clinical efficacy compared with Western medicine, acupuncture and placebo in treating FC, with a low incidence of adverse effects. However, due to the limitations of the included studies, high-quality, large-sample RCTs are still needed to verify the long-term efficacy and safety of ACE.Systematic review registrationIdentifier INPLASY202570017.